2013
DOI: 10.1002/cne.23369
|View full text |Cite
|
Sign up to set email alerts
|

Central projections of lagenar primary neurons in the chick

Abstract: Perception of linear acceleration and head position is the function of the utricle and saccule in mammals. Nonmammalian vertebrates possess a third otolith endorgan, the macula lagena. Different functions have been ascribed to the lagena in arboreal birds, including hearing, equilibrium, homing behavior, and magnetoreception. However, no conclusive evidence on the function of the lagena in birds is currently available. The present study is aimed at providing a neuroanatomical substrate for the function of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The problem for a hypothesis suggesting that the magnetic activation in PrV and SpV could have come from putative magnetoreceptors in the vestibular system (lagena) is that, although the vast majority of neuronal connections within the brain show reciprocal innervations, no projections backwards from the N. basalis to either the superior vestibular nuclei (D in figure 5) or to PrV (E in figure 5) have been described yet. However, a recent neuronal tracing study in domestic chicken reported a direct projection from the lagena not only to medial and spinal vestibular nuclei [47] (F in figure 5), but also to SpV (G in figure 5). Thus, a putative neuronal connection seems to exist in a different bird species, which could support an explanation, where the magnetically induced neuronal ZENK activation we observed in PrV or SpV would be owing to primary magnetic sensors located in the lagena.…”
Section: Discussionmentioning
confidence: 96%
“…The problem for a hypothesis suggesting that the magnetic activation in PrV and SpV could have come from putative magnetoreceptors in the vestibular system (lagena) is that, although the vast majority of neuronal connections within the brain show reciprocal innervations, no projections backwards from the N. basalis to either the superior vestibular nuclei (D in figure 5) or to PrV (E in figure 5) have been described yet. However, a recent neuronal tracing study in domestic chicken reported a direct projection from the lagena not only to medial and spinal vestibular nuclei [47] (F in figure 5), but also to SpV (G in figure 5). Thus, a putative neuronal connection seems to exist in a different bird species, which could support an explanation, where the magnetically induced neuronal ZENK activation we observed in PrV or SpV would be owing to primary magnetic sensors located in the lagena.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the anatomical aspect of the vestibular and acoustic ganglia, studies of otic neuron segregation and axonal projections in both mammals and birds have considered the division of the vestibular ganglion into two portions, one superior portion and another inferior portion [ 10 , 54 , 73 , 74 ]. Judging from a preliminary anatomical study of the vestibular and acoustic ganglia in chicks using HuC/D immunoreactions, which labeled the postmitotic neuronal phenotypes [ 75 ], the vestibular ganglion can be considered to be divided into two portions (lobes), anterior ( a -VG) and posterior ( p -VG) ( Figure 1 a,b; Supplementary Figure S1 ), according to the anterior-to-posterior axis of the hindbrain.…”
Section: Resultsmentioning
confidence: 99%
“…All sensory elements of this intricate organ are composed of mechano-transducing hair cells that transform mechanical stimuli into electric signals and supporting cells that offer cellular and mechanical support to the hair cells, with both types of cells having an extremely specific cytoarchitectonic arrangement [ 6 , 7 ]. Neurons of the acoustic and vestibular ganglia connect the hair cells of the developing otic epithelium with their targets, the vestibular and auditory nuclei in the hindbrain, with a topographically well-defined pattern of connections [ 8 , 9 , 10 , 11 ]. Both hair cells and otic neuroblasts have a clonal relationship, these cells being derived from a population of common progenitor cells [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological recordings in fish and frogs have demonstrated that lateral cerebellar regions have neurons that respond to head rotation (Ansorge & Grüsser‐Cornehls, ; Blanks, Precht, & Giretti, ; Montgomery, ). Although these reports suggest that the myelinated commissure can, in part, mediate vestibular signals, CN VIII also carries afferents from several other sensory neuroepithelia in the turtle's temporal bone (papilla neglecta, sacculus, utricle, lagena, and the basilar papilla) that mediate nonvestibular signals (Mahmoud, Reed, & Maklad, ).…”
Section: Discussionmentioning
confidence: 99%